O caráter discursivo e polifônico da homilia católica: uma análise dentro do campo religioso. - Silva, Rita de Kássia Pontes (2022)
One of the first objectives of the homily is to collaborate so that the Christian word is better understood by the assembled faithful. For Buyst (2001) the homily serves to encourage, animate, exhort, console and speak of the mysteries of the faith, leading those who hear it to an active and conscious participation, and this is the function of the priest, who also depends on the participation of the faithful during the homily so that it has effective results to “bear fruit”. It is the message sent that demands a response, and that makes us, based on Bakhtin (2000), define it as a discursive genre, as it constitutes, in fact, a stable utterance from the liturgical point of view, since its purpose is to understand of the message transmitted to the faithful by the celebrant and because it is constituted from the relationships established with other statements, including the texts of the Bible. The purpose of the homily is, then, the application of the biblical message to the here and now of human life. Viewed here as an important symbolic asset, as Bourdieu claims, the homily can contribute to understanding the religious transit pointed out in several studies based on census data. Currently, what is perceived is a variety of situations: many priests who manage to express themselves well and people understand the message sent, others who cannot convey the message in an understandable way, not awakening people to an effective responsive understanding. In the case of language, especially that of the priests, it is clear that the years of study for theological and philosophical formation, the documents of the Church, lead them to use an erudite language. How then can the priest make common the language used in homilies? It is necessary for the sender to put himself in the place of the listener to ask himself what he will understand. As part of a religious cult, it is not just any discourse, but it is legitimized by the coercive force of religion and faith. We hope, with this work, to present the constitutive aspects that characterize the homily as a discursive and polyphonic genre, as well as the communicative aspects and the ability of this discourse to influence and modify people's behaviors and attitudes, highlighting the homily as an important symbolic asset in this power game presented within the religious field in the country.